Deficient leucocyte antisedimentation is related to post-stroke infections and outcome. Issue 11 (27th October 2008) - Molnar, T; Peterfalvi, A; Szereday, L; Pusch, G; Szapary, L; Komoly, S; Bogar, L; Illes, Z
Abstract : Background: Patients with stroke are more susceptible to infections, suggesting possible deficiencies of early immune responses, particularly of leucocytes. Aims: To serially examine leucocyte antisedimentation rate (LAR), a simple test to detect activation of leucocytes, and correlate it with S100β, procalcitonin and outcome in patients with acute ischaemic events. Methods: Venous blood samples were taken from 61 healthy volunteers and 49 patients with acute ischaemic events (acute ischaemic stroke (AIS), n = 38; transient ischaemic attack (TIA), n = 11) within 6 hours, at 24 and 72 hours after onset of symptoms. Results: LAR was significantly higher in acute ischaemic events compared to controls within 6 hours after onset of stroke regardless of post-stroke infections. In addition, the increase of LAR was delayed and attenuated in TIA in contrast to AIS. A deficiency in early increase of LAR was associated with post-stroke infections and a poor outcome, measured by the Glasgow Outcome Scale in AIS. There was a positive correlation between LAR and S100β at 72 hours after the onset of ischaemic stroke. Increased levels of S100β at 24 and 72 hours after stroke were associated with poor outcome. Conclusions: An early activation of leucocytes indicated by an increase of LAR is characteristic of acute ischaemic cerebrovascular events. A delayed and ameliorated leucocyte activation represented by LAR is characteristic of TIA in contrast to stroke. Deficient early activation predisposes to post-stroke infections related to poor outcome. In addition, the extent of tissue injury correlates with the magnitude of innate immune responses.